Osteopontin Promotes Hepatic Progenitor Cell Expansion and Tumorigenicity via Activation of β-Catenin in Mice. (23rd June 2015) - Liu, Yingying; Cao, Lei; Chen, Rui; Zhou, Xuyu; Fan, Xiaoyu; Liang, Yingchao; Jia, Rongjie; Wang, Hao; Liu, Guoke; Guo, Yajun; Zhao, Jian
Abstract: Upregulation of osteopontin (OPN) has been found in hepatic progenitor cells (HPCs) in several liver diseases with portal biliary proliferation. Here, we investigated the role of HPC-derived autocrine OPN in regulating HPC expansion, migration, and hepatocarcinogenesis in mice. Five-week-old, weighing between 18 and 20 g of either wild type (WT) or OPN gene knockout ( OPN -KO) male mice were treated with modified choline-deficient, ethionine-supplemented diet (modified choline-deficient [MCDE]) for 2 weeks to induce HPC production, or 6–12 months to induce tumorigenesis. Epithelial cell adhesion molecule EpCAM + CD45 − cells isolated from mouse liver and liver epithelial progenitor cells were used for in vitro study. OPN was blocked by specific antibody or RNAi-mediated silence to investigate the role of OPN. To evaluate correlation between OPN expression and β-catenin activity, expressions of OPN and β-catenin were assessed in human liver cancer specimens. We found autocrine OPN promotes HPC expansion and migration by decreasing membranous E-cadherin and increasing free cytoplasmic β-catenin via binding to αv integrin and activating Src activity. Depletion of OPN significantly attenuated MCDE-induced hepatocarcinogenesis. Clinical evidence revealed a strong correlation of high OPN expression with cytoplasmic/nuclear expression of β-catenin in 43 cases of human combined hepatocellular carcinoma and cholangiocarcinoma and mixed intrahepatic cholangiocarcinoma and 80 cases of hepatocellular carcinoma. Our results indicate that autocrine OPN plays a crucial role in HPC expansion, migration, and subsequent oncogenic transformation of HPCs, which may provide a new insight into hepatocarcinogenesis. Stem Cells   2015;33:3569–3580